A PLATELET REGENERATION WHILE EATING PAPAYA - BHATT, ANIR; Shah, Prof Ravish (International Journal of Multidisciplinary Research and Studies, 2021)
The different corridor of the Papaya (Carica papaya Linn.) belonging to the family Caricaceae similar as leaves, seeds, latex, and fruit retain excellent medicinal parcels for the treatment of different affections. The stem, splint, and fruit of papaya contain plenitude of latex. The latex from callow fruit contains the enzyme papain, other factors include admixture of cysteine end peptidases, chitinases, and an asset of serine protease, alkaloids, glycosides, flavanoids, saponins, tannins, phenols, and steroids. This evaluation focuses on the nutritive merit, phyto-chemical component, tocopherol and free comprehensive scavenging exertion, medicaments for dengue fever, and anticancer exertion of paw-paw. Papaya acts as an amulti-faceted factory. It’s also essential to identify the medium of the factory composites and study the active principle of the excerpt. It’s proposed to involve the paw-paw in our diet as fruit mixed greens, fruit sap, splint excerpt, a decoction prepared through paw-paw leaves, etc.(31)